Method for regenerating positive electrode active material and positive electrode active material regenerated therefrom
By using water containing ionic solid salt to clean residual component F during the recovery process of the positive electrode active material of lithium-ion batteries, the problems of foreign substance residues and environmental pollution are solved, and efficient, environmentally friendly and safe regeneration of positive electrode active material is achieved.
Patent Information
- Application Number
- JP2023551227
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-10-21
- Filing Date
- 2022-08-24
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2042-08-24
AI Technical Summary
In the prior art, when recycling the positive electrode active material of lithium-ion batteries, there are problems such as the residue of foreign substances that lead to degradation of battery output performance, the use of acids leads to environmental pollution and high costs, and the inability to avoid the disposal of metal elements.
By cleaning with water containing ionic solid salt in the heat treatment step, the residual F component on the surface of the positive electrode active material is removed, the loss of functional coating is avoided, and the safe recycling and regeneration of the positive electrode active material is achieved by using an acid-free and organic solvent-free method.
It significantly improves the output performance of the battery, reduces environmental pollution and production costs, and avoids the disposal of metal elements, while ensuring the integrity and recyclability of the battery active materials.
Smart Images

Figure 0007654814000002 
Figure 0007654814000003 
Figure 0007654814000004
Abstract
Description
[Technical Field]
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims the benefit of priority based on Korean Patent Application No. 10-2021-0141106, dated October 21, 2021, and all contents disclosed in the documents of that Korean patent application are incorporated herein by reference.
[0002] The present invention relates to a method for regenerating a cathode active material and a cathode active material regenerated therefrom. More specifically, the present invention relates to a method for regenerating a cathode active material by thoroughly removing fluorine components generated on the surface of the regenerated cathode active material during a heat treatment step using water containing an ionic solid salt, thereby reducing the loss of the fluorine compound layer formed on the initial raw material, thereby significantly improving the battery's rate performance. The method is environmentally friendly because it does not use acid, and does not require neutralization or wastewater treatment, thereby reducing process costs. The method regenerates the cathode active material without decomposition, so no metal elements are discarded, and does not dissolve the current collector, allowing it to be recovered. The method does not use organic solvents, so it is safe and does not generate toxic gases or pose a risk of explosion. The method uses processes that are easy to manage, such as heat treatment and precipitation, making it suitable for mass production. The present invention also relates to a regenerated cathode active material regenerated therefrom, which has excellent electrochemical performance, resistance characteristics, and capacity characteristics. [Background technology]
[0003] A lithium secondary battery is generally composed of a positive electrode in which a positive electrode active material layer is coated on a metal foil such as aluminum, a negative electrode in which a negative electrode active material layer is coated on a metal foil such as copper, a separator that prevents the positive and negative electrodes from mixing, and an electrolyte that allows lithium ions to move between the positive and negative electrodes.
[0004] The positive electrode active material layer mainly uses a lithium-based oxide as an active material, and the negative electrode active material layer mainly uses a carbon material as an active material. However, the lithium-based oxide generally contains rare metals such as cobalt, nickel, or manganese. Therefore, much research has been conducted into recovering and reusing rare metals from the positive electrodes of lithium secondary batteries that are discarded after use or from positive electrode scraps generated in the manufacturing process of lithium secondary batteries (hereinafter referred to as "waste positive electrodes").
[0005] Conventional techniques for recovering rare metals from used positive electrodes mostly involve dissolving the used positive electrodes in hydrochloric acid, sulfuric acid, or nitric acid, then extracting cobalt, manganese, nickel, etc. with an organic solvent and using them again as raw materials for synthesizing positive electrode active materials.
[0006] However, the method of extracting rare metals using acid has environmental pollution problems, and because it requires a neutralization process and a wastewater treatment process, the process costs increase significantly, making it difficult to ensure economic viability in the process of recovering high-purity lithium, the main metal in positive electrode active materials.
[0007] To overcome these drawbacks, direct recycling methods have recently been studied to directly regenerate cathode active materials from waste cathodes without decomposing them. These methods can be broadly divided into four types: calcination, solvent dissolution, aluminum foil dissolution, and crushing and screening.
[0008] However, although the calcination method is simple, it has drawbacks in that foreign matter that reduces the output performance of the battery is generated on the surface of the regenerated positive electrode active material, waste gas is generated, and energy consumption is high.
[0009] In addition, although the solvent dissolution method can produce recycled cathode active materials with a relatively clean surface, it has the disadvantages of poor stability and the need for an expensive solvent recovery process because the solvent used to dissolve the binder, such as N-methyl-2-pyrrolidone (NMP), is a toxic gas and has the risk of explosion.
[0010] In addition, the aluminum foil dissolving method has good process stability, low process costs, and easy binder removal, but has drawbacks in that it generates foreign matter that is difficult to remove on the surface of the recycled cathode active material, and hydrogen gas is generated during the aluminum foil removal process, which may pose an explosion risk.
[0011] Finally, the crushing and screening method has the advantage of being the simplest process, but has the disadvantages that it is difficult to completely separate the current collector from the cathode active material, the particle size distribution of the cathode active material changes during the crushing process, and the binder remains, which deteriorates the battery characteristics of the recycled cathode active material.
[0012] On the other hand, the water washing process used in the direct recycling method of recycled cathode active material without decomposition of the cathode active material from waste cathodes requires excessive washing water, which can lead to the loss of functional coating layers, such as the F compound layer, formed on the initial cathode active material raw material. The functional coating layers are applied to improve the long-life and high-voltage characteristics of the cathode active material.
[0013] Therefore, there is an urgent need to develop a method for safely and inexpensively recycling a cathode active material with improved output performance without discarding metal elements from used cathodes or losing the functional coating layer, in an environmentally friendly manner. Summary of the Invention [Problem to be solved by the invention]
[0014] To address the above-mentioned problems of the prior art, the present invention provides a method for regenerating a cathode active material by thoroughly removing residual F components generated on the surface of the regenerated cathode active material during the heat treatment step using water containing an ionic solid salt, thereby preventing the loss of functional coating layers such as the F compound layer formed on the initial raw material, thereby significantly improving the rate performance of the battery. This method is environmentally friendly because it does not use acid, and reduces process costs because it does not require neutralization or wastewater treatment. The method regenerates the cathode active material without decomposition, so there are no discarded metal elements, and the current collector is not dissolved, allowing it to be recovered. The method is safe because it does not use organic solvents, so there is no risk of toxic gas generation or explosion. The method is suitable for mass production because it uses processes that are easy to manage, such as heat treatment and sedimentation.
[0015] Another object of the present invention is to provide a positive electrode active material that is excellent in electrochemical performance, resistance characteristics, and capacity characteristics.
[0016] The above and other objects of the present invention can all be achieved by the present invention described below. [Means for solving the problem]
[0017] In order to achieve the above object, the present invention provides a method for regenerating a positive electrode active material, including the steps of: (a) heat-treating a used positive electrode, which includes a current collector and a positive electrode active material layer coated on the current collector, in air at 300 to 650°C to recover the positive electrode active material; (b) washing the recovered positive electrode active material with water containing an ionic solid salt; and (c) adding a lithium precursor to the washed positive electrode active material and annealing the resulting material in air at 400 to 1000°C.
[0018] The discarded positive electrodes in step (a) may preferably be positive electrodes separated from used and discarded lithium secondary batteries, defective positive electrode sheets generated in the manufacturing process of lithium secondary batteries, or positive electrode scraps remaining after punching out positive electrode plates from positive electrode sheets.
[0019] The positive electrode active material may preferably include at least one selected from the group consisting of lithium cobalt oxides such as LiCoO2, lithium manganese oxides such as LiMnO2 or LiMn2O4, lithium iron phosphate compounds such as LiFePO4, lithium nickel cobalt aluminum oxide (NCA), lithium nickel oxides such as LiNiO2, nickel manganese-based lithium composite metal oxides in which part of the nickel (Ni) in the lithium nickel oxide is substituted with manganese (Mn), and NCM-based lithium composite transition metal oxides in which part of the nickel (Ni) in the lithium nickel oxide is substituted with manganese (Mn) and cobalt (Co).
[0020] The ionic solid salt may preferably be one or more selected from the group consisting of MgSO4, Mg(NO3)2, and Ca(NO3)2.
[0021] In the washing in the step (b), preferably, water containing an ionic solid salt can be used in an amount of 1 to 40 times by weight of the recovered positive electrode active material.
[0022] In the step (b), the water containing the ionic solid salt may preferably be an aqueous solution in which the ionic solid salt is dissolved in water, or may be in a state in which the ionic solid salt is dispersed in water in the form of a powder.
[0023] In the step (b), the ionic solid salt preferably reacts with LiF on the surface of the positive electrode active material to form a complex compound.
[0024] The ionic solid salt used in step (b) can be preferably used in an amount of 0.5 to 2 moles per mole of LiF produced in the recovered positive electrode active material.
[0025] The ionic solid salt used in step (b) can be preferably used in an amount of 1.5 to 5.5 parts by weight per 100 parts by weight of the recovered positive electrode active material.
[0026] In the step (b), the washing can preferably include stirring the recovered positive electrode active material with water containing an ionic solid salt.
[0027] The step (b) may preferably include a step of drying the washed positive electrode active material.
[0028] The lithium precursor in step (c) may preferably be one or more selected from the group consisting of LiOH, Li2CO3, LiNO3 and Li2O.
[0029] The lithium precursor in step (c) may be added preferably in an amount that is at least reduced from the molar ratio of lithium in the positive electrode active material in step (a), based on the amount of lithium in the washed positive electrode active material.
[0030] The annealing temperature in step (c) may preferably be a temperature above the melting point of the lithium precursor.
[0031] The method for regenerating a positive electrode active material may preferably include the step of (d) mixing the annealed positive electrode active material with a coating agent, and then coating the mixed material by heat treatment at 100 to 1200°C.
[0032] The present invention also provides a recycled positive electrode active material produced by the method for recycling a positive electrode active material.
[0033] The surface of the regenerated positive electrode active material may preferably be coated with a coating agent containing a metal oxide or a metal salt containing carbon. [Effects of the Invention]
[0034] According to the present invention, residual F components generated on the surface of the regenerated cathode active material during the heat treatment step are thoroughly removed using water containing an ionic solid salt, minimizing the loss of functional coating layers such as the F compound layer formed on the initial raw material, thereby significantly improving rate performance. Since no acid is used, the method is environmentally friendly and eliminates the need for neutralization and wastewater treatment, thereby reducing process costs. Since the cathode active material is regenerated as is without decomposition, no metal elements are discarded. Since the current collector is not dissolved, it can be recovered. Since no organic solvent is used, there is no risk of toxic gas generation or explosion. The method uses processes that are easy to manage, such as heat treatment and sedimentation, making it suitable for mass production. The present invention also provides a regenerated cathode active material having excellent electrochemical performance, resistance characteristics, and capacity characteristics.
[0035] The following drawings attached to this specification illustrate embodiments of the present invention and, together with the detailed description to be given below, serve to further understand the technical concept of the present invention. Therefore, the present invention should not be interpreted as being limited to the matters depicted in these drawings. [Brief explanation of the drawings]
[0036] [Figure 1] FIG. 10 is a diagram showing positive electrode scraps that are discarded after cutting electrode plates from a positive electrode sheet. [Figure 2] 1 is a graph showing the results of cell evaluation of a new positive electrode active material of a reference example and a recycled positive electrode active material produced in Comparative Example 1, illustrating rate performance as a function of the number of cycles. [Figure 3] 1 is a graph showing the results of cell evaluation of the recycled positive electrode active materials prepared in Comparative Examples 1 and 2, illustrating the rate performance as a function of the number of cycles. [Figure 4] 1 is a graph showing the results of cell evaluation of the recycled positive electrode active materials prepared in Example 1 and Comparative Example 3, illustrating the rate performance as a function of the number of cycles. [Figure 5]1 is a graph showing the results of cell evaluation of the recycled positive electrode active materials prepared in Example 2 and Comparative Example 3, illustrating the rate performance as a function of the number of cycles. [Figure 6] 1 is a graph showing the results of cell evaluation of the recycled positive electrode active materials prepared in Examples 1 and 3 and Comparative Example 3, illustrating the rate performance as a function of the number of cycles. [Figure 7] 1 is a graph showing the results of cell evaluation of the recycled positive electrode active materials prepared in Examples 1 and 4 and Comparative Example 3, illustrating the rate performance as a function of the number of cycles. [Figure 8] 1 is a graph showing the results of cell evaluation of the recycled positive electrode active materials prepared in Examples 1 and 5 and Comparative Example 3, illustrating the rate performance as a function of the number of cycles. [Figure 9] 1 is a flowchart illustrating a process for regenerating a positive electrode active material according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE INVENTION
[0037] The inventors were researching a direct recycled method for recycling cathode active material from waste cathodes without decomposing it. They discovered that recovering cathode active material from cathode scraps generated during the lithium secondary battery manufacturing process using a calcination method and then washing the recovered cathode active material in a modification process with water containing an ionic solid salt minimizes the loss of the functional coating layer formed on the initial raw material and improves the battery characteristics of the recycled cathode active material. Based on this finding, they continued their research and completed the present invention.
[0038] The method for regenerating a positive electrode active material and the positive electrode active material regenerated therefrom will now be described in detail.
[0039] However, the terms and words used in this specification and claims should not be interpreted as being limited to their ordinary or dictionary meanings, but should be interpreted as meanings and concepts that correspond to the technical idea of the present invention, based on the principle that the inventor can appropriately define the concept of terms in order to best describe his or her invention. Therefore, it should be understood that the embodiments described in this specification and the configurations shown in the drawings are merely one embodiment of the present invention and do not fully represent the technical idea of the present invention, and therefore various equivalents and modifications that can replace them may exist, and they may be arranged, substituted, combined, separated, or designed in various other configurations.
[0040] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention belongs.
[0041] Method for regenerating positive electrode active material The method for regenerating a positive electrode active material of the present invention is characterized by comprising the steps of: (a) heat-treating a waste positive electrode comprising a current collector and a positive electrode active material layer coated thereon at 300 to 650°C in air to recover the positive electrode active material; (b) washing the recovered positive electrode active material with water containing an ionic solid salt; and (c) adding a lithium precursor to the washed positive electrode active material and annealing the mixture in air at 400 to 1000°C. In this case, residual F components generated on the surface of the regenerated positive electrode active material during the heat-treatment step are thoroughly removed with the water containing the ionic solid salt, thereby significantly reducing the amount of wastewater generated and simultaneously improving the output performance (rate) of the battery. It has the advantages of significantly improving the catalytic performance, being environmentally friendly because it does not use acids, reducing process costs because it does not require neutralization or wastewater treatment, regenerating the cathode active material without decomposing it, eliminating the waste of metal elements, and not dissolving the current collector, making it possible to recover it, eliminating the risk of toxic gas generation or explosion because it does not use organic solvents, and using processes that are easy to manage, such as heat treatment and sedimentation, making it suitable for mass production.
[0042] (a) A step of recovering a positive electrode active material from a waste positive electrode The step (a) of recovering a positive electrode active material from a used positive electrode according to the present invention may preferably be a step of recovering the positive electrode active material by heat-treating a used positive electrode including a current collector and a positive electrode active material layer coated thereon in air at 300 to 650°C. In this case, the process is simple and has the effect of completely removing the binder, conductive material, and current collector.
[0043] The discarded positive electrodes may preferably be positive electrodes separated from used and discarded lithium secondary batteries, defective positive electrode sheets generated in the manufacturing process of lithium secondary batteries, or positive electrode scraps, and more preferably positive electrode scraps remaining after punching out positive electrode plates from positive electrode sheets.
[0044] The positive electrode active material layer in step (a) may preferably include a positive electrode active material, a binder, and a conductive material.
[0045] The positive electrode active material may be at least one selected from the group consisting of lithium cobalt oxides such as LiCoO (hereinafter referred to as "LCO"), lithium manganese oxides such as LiMnO or LiMnO, lithium iron phosphate compounds such as LiFePO, lithium nickel cobalt aluminum oxide (NCA), lithium nickel cobalt aluminum oxide (NCA), lithium nickel oxides such as LiNiO, nickel manganese-based lithium composite metal oxides in which part of the nickel (Ni) in the lithium nickel oxide is substituted with manganese (Mn), and NCM-based lithium composite transition metal oxides in which part of the nickel (Ni) in the lithium nickel oxide is substituted with manganese (Mn) and cobalt (Co). More preferably, the positive electrode active material is a nickel manganese-based lithium composite metal oxide, an NCM-based lithium composite transition metal oxide, or a mixture thereof. In this case, excellent reversible capacity and thermal stability can be achieved.
[0046] As a specific example, the positive electrode active material may be represented by the following Chemical Formula 1: [Chemical formula 1] Li aNi x Mn y Co z M w O 2+δ (In Chemical Formula 1 above, M includes one or more selected from the group consisting of B, W, Al, Ti, and Mg, and 1 < a ≤ 1.1, 0 < x < 0.95, 0 < y < 0.8, 0 < z < 1.0, 0 ≤ w ≤ 0.1, -0.02 ≤ δ ≤ 0.02, and x + y + z + w = 1. ) It may be a compound represented by
[0047] The conductive material may be, for example, a carbon-based conductive material, and preferably, it may be carbon black, carbon nanotube (CNT), or a mixture thereof.
[0048] The binder may be, for example, a polymer binder, and preferably, it may be polyvinylidene fluoride (PVdF), acrylonitrile-butadiene rubber (NBR), or a mixture thereof, and more preferably, it may be polyvinylidene fluoride.
[0049] The heat treatment temperature is preferably 400 to 60℃, more preferably 500 to 600℃, and even more preferably 530 to 580℃. Within this range, there is an advantage that the current collector does not melt and only the binder etc. is removed, so that the positive electrode active material can be easily separated from the current collector.
[0050] The heat treatment time is preferably 10 minutes to 5 hours, more preferably 30 minutes to 5 hours, even more preferably 30 minutes to 2 hours, and even more preferably 30 minutes to 1 hour. Within this range, there is an advantage that the current collector does not melt and only the binder etc. is removed, so that the positive electrode active material can be easily separated from the current collector.
[0051] In this description, the heat treatment time is the time treated at the heat treatment temperature, and the time to reach the heat treatment temperature is not calculated.
[0052] Figure 1 below shows the cathode scrap that is discarded after cutting the cathode plates from the cathode sheet.
[0053] 1, a long sheet-shaped positive electrode current collector (aluminum foil 10) is coated with a positive electrode active material layer 20 containing a positive electrode active material, a conductive material, a binder, etc. to produce a positive electrode sheet 30, which is then punched to a predetermined size to produce a positive electrode plate 40, with the remaining portion being generated as positive electrode scrap 50. Punching is one method of cutting the positive electrode sheet.
[0054] In addition, the positive electrode active material layer 20 is formed by coating a slurry containing a positive electrode active material, a conductive material, a binder, a solvent, etc., on the aluminum foil 10. Since the slurry is very sensitive to environmental factors such as temperature, it is very difficult to determine the coating conditions. Therefore, waste positive electrode sheets are generated until the conditions for manufacturing a positive electrode sheet 30 of desired quality are found through predetermined tests.
[0055] For reference, in the following examples, scrap positive electrodes were used as waste positive electrodes.
[0056] (b) Step of cleaning the positive electrode active material (surface modification step) The step (b) of washing the cathode active material according to the present invention may preferably be a step of washing the recovered cathode active material with water containing an ionic solid salt. In this case, residual F components, specifically LiF, generated on the surface of the recycled cathode active material during the heat treatment step are completely removed, and loss of the functional coating layer formed on the initial raw material is minimized, thereby significantly improving the output performance of the battery.
[0057] The ionic solid salt may be, for example, one or more selected from the group consisting of MgSO4, Mg(NO3)2, and Ca(NO3)2, preferably MgSO4, Mg(NO3)2, or a mixture thereof, and more preferably MgSO4. In this case, it has the effect of completely removing F components remaining on the surface of the recycled positive electrode active material and minimizing the loss of the functional coating layer formed on the initial raw material, thereby significantly improving the output performance of the battery.
[0058] The MgSO4 may preferably be anhydrous MgSO4, the Mg(NO3)2 may preferably be Mg(NO3)2·6H2O, and the Ca(NO3)2 may preferably be Ca(NO3)2·4H2O.
[0059] The ionic solid salt in step (b) can be used in an amount of preferably 0.5 to 2 mol, more preferably 0.5 to 1.5 mol, and even more preferably 0.5 to 1 mol, relative to 1 mol of LiF produced in the recovered positive electrode active material. Within this range, the reaction rate is appropriate, and the ionic solid salt reacts with LiF on the surface of the positive electrode active material to form a complex compound that can be easily removed, thereby significantly improving the output performance of the battery.
[0060] In this description, the content of LiF formed in the recovered positive electrode active material can be measured by ICP-OES analysis. Specifically, an ICP-OES analyzer (Inductively Coupled Plasma Optical Emission Spectroscophotometer) can be used to measure the content of LiF formed in the recovered positive electrode active material, the ratio of lithium to other metals in the active material, and the content (mg / kg) of specific elements such as F. In this case, measurements can be made using a general ICP-OES analyzer commonly used in laboratories, and there is no deviation due to the measurement device or method.
[0061] The ionic solid salt used in step (b) is preferably 1.5 to 5.5 parts by weight, more preferably 2 to 5 parts by weight, and even more preferably 2 to 4.5 parts by weight, per 100 parts by weight of the recovered positive electrode active material. Within this range, the ionic solid salt is highly effective in removing the F component remaining on the surface of the regenerated positive electrode active material, thereby significantly improving the output performance of the battery.
[0062] In the washing step (b), the water containing the ionic solid salt is preferably used in an amount 1 to 40 times by weight, more preferably 10 to 35 times by weight, and even more preferably 25 to 32 times by weight, of the recovered cathode active material. Within this range, the F component remaining on the surface of the recycled cathode active material after the heat treatment step is completely removed, and the loss of the functional coating layer formed on the initial raw material is minimized, thereby significantly improving the output performance of the battery.
[0063] In step (b), the water containing the ionic solid salt may be preferably an aqueous solution in which the ionic solid salt is dissolved in water, or a powder-like dispersion of the ionic solid salt in water. In this case, the F component remaining on the surface of the regenerated cathode active material after the heat treatment step is completely removed, and the loss of the functional coating layer formed on the initial raw material is minimized, thereby significantly improving the output performance of the battery.
[0064] The state in which the ionic solid salt is dispersed in water in a powder form may preferably be such that the powdered ionic solid salt is added to water together with the recovered positive electrode active material, which has the effect of shortening the time.
[0065] The water may be, for example, one or more selected from the group consisting of tap water, deionized water (DIW), first distilled water, second distilled water, and third distilled water.
[0066] In the step (b), the ionic solid salt preferably forms a complex compound on the surface of the positive electrode active material, which has the effect of significantly improving the output performance of the battery.
[0067] In step (b), the ionic solid salt can more preferably react with LiF or the like remaining on the surface of the positive electrode active material after the heat treatment step to form a complex compound. In this case, the ionic solid salt has an excellent effect of removing LiF or the like, which has the effect of significantly improving the output performance of the battery.
[0068] For example, the complex compound may be precipitated on the surface of the positive electrode active material or in a solution.
[0069] For example, when MgSO4 is used as the ionic solid salt, MgSO4 and LiF are dissociated and form a complex compound MgF through the reaction pathway shown in the following chemical formula 2: x Form.
[0070] [Chemical formula 2] MgSO4+2LiF=MgF2+Li2SO4
[0071] The washing in step (b) may preferably be a step of stirring and washing the recovered positive electrode active material and water containing an ionic solid salt. In this case, as a step of modifying the surface of the positive electrode active material, it has the effect of removing foreign matter such as LiF or metal fluorides generated on the surface of the positive electrode active material in the previous heat treatment step.
[0072] The stirring may be carried out, for example, at 300 to 700 rpm for 5 to 20 minutes, and preferably at 400 to 600 rpm for 8 to 15 minutes. Within this range, all foreign matter such as LiF or metal fluorides generated on the surface of the positive electrode active material is removed, and there is no excessive elution of lithium, which is advantageous in that the capacity characteristics of the battery are excellent.
[0073] In the step (b), washing can be preferably performed after the stirring or mixing is completed by rinsing with washing water in an amount of 5 to 15 times, more preferably 7 to 12 times, the amount of the recovered positive electrode active material. In this case, the capacity characteristics of the battery can be improved.
[0074] The washing water may preferably be triple distilled water.
[0075] In step (b), the washing step may preferably include a step of recovering the solid cathode active material by filtering or decanting the supernatant after the rinsing step, followed by drying. In this case, the step of adding the lithium precursor can be optimized.
[0076] For example, the filtration can be performed using filter paper, preferably 0.1 to 0.7 μm filter paper, and more preferably 0.2 to 0.4 μm filter paper, which has the advantage of making it easier to remove impurities.
[0077] The drying can be carried out preferably at 70 to 200°C, more preferably at 20 to 130°C, until there is no further change in weight, for example, for 1 to 24 hours. Within this range, the moisture contained in the washed positive electrode active material can be effectively removed.
[0078] (c) adding a lithium precursor to the positive electrode active material and then annealing the material; The step (c) of adding a lithium precursor to the positive electrode active material and then annealing the material may preferably be a step of adding a lithium precursor to the washed positive electrode active material and annealing the material in air at 400 to 1000°C. In this case, the battery characteristics of the regenerated positive electrode active material can be improved by improving the crystallinity, such as by increasing the crystallinity or restoring the crystal structure.
[0079] After adding the lithium precursor to the (c) positive electrode active material, the mixture may be sieved, preferably one to three times, more preferably twice, through a sieve with a mesh size of #325, before annealing. In this case, the positive electrode active material and the lithium precursor can be advantageously mixed uniformly.
[0080] The lithium precursor in step (c) may preferably be one or more selected from the group consisting of LiOH, Li2CO3, LiNO3 and Li2O.
[0081] The lithium precursor in step (c) is preferably added in an amount that is at least the molar ratio of lithium in the positive electrode active material in step (a) reduced based on the amount of lithium in the washed positive electrode active material, and more preferably, in an amount that results in a lithium molar ratio of 0.0001 to 0.2 relative to the molar ratio of lithium in the positive electrode active material in step (a).Within this range, the deficient lithium in the regenerated positive electrode active material is replenished, and crystallinity is improved, such as by increasing crystallinity or restoring the crystal structure, thereby improving the battery characteristics of the regenerated positive electrode active material.
[0082] The lithium precursor in step (c) may be added in an amount that provides 0.1 to 40 mol% of lithium based on a total of 100 mol% of lithium in the cathode active material in step (a), more preferably 1 to 15 mol%, and even more preferably 1 to 11 mol% of lithium. Within this range, no residual precursor that may increase resistance remains in the regenerated cathode active material, which is very useful for improving battery characteristics.
[0083] The annealing temperature in step (c) can be adjusted within a limited range depending on the melting point of the lithium precursor. For example, since the melting point of Li2CO3 is 723°C, annealing can be preferably performed at 700 to 900°C, more preferably 710 to 780°C. Since the melting point of LiOH is 462°C, annealing can be preferably performed at 400 to 800°C, more preferably 550 to 800°C, and even more preferably 650 to 780°C. Within this range, the crystal structure is restored, which has the effect of improving the output performance of the battery.
[0084] The annealing temperature in step (c) may preferably be a temperature exceeding the melting point of the lithium precursor. However, if the annealing temperature exceeds 1000°C, thermal decomposition of the positive electrode active material may occur, resulting in a decrease in battery performance.
[0085] (d) Mixing with a coating agent, then heat treating and coating The step (d) of mixing a coating agent and then heat-treating to coat the mixture according to the present invention is an optional step, and preferably, the step of mixing the annealed cathode active material of step (c) with a coating agent and then heat-treating the mixture at 100 to 1200°C to coat the mixture. In this case, the structural stability and electrochemical performance can be improved while maintaining the properties of the cathode active material itself.
[0086] The coating agent may be, for example, a metal oxide or a metal salt containing carbon.
[0087] The carbon-containing metal salt may be, for example, a metal carbonate compound.
[0088] The metal contained in the metal oxide or metal salt containing carbon is preferably a metal oxide or metal salt containing one or more selected from the group consisting of B, W, Al, Ti, Mg, Ni, Co, Mn, Si, Zr, Ge, Sn, Cr, Fe, V, and Y, and more preferably a metal oxide or metal salt containing one or more selected from the group consisting of B, W, Al, Ti, and Mg. In this case, there is an effect of replenishing or restoring metals other than lithium or surface coating layers lost during the current collector separation process and the positive electrode active material surface modification process.
[0089] The heat treatment temperature may be preferably 100 to 1000°C, more preferably 200 to 1000°C, and even more preferably 200 to 500°C. Within this range, the properties of the positive electrode active material itself are maintained as they are, while the structural stability and electrochemical performance are improved.
[0090] Specifically, when the coating agent contains B, BW, B-Ti, or BW-Ti, the heat treatment temperature is preferably 200 to 500°C.
[0091] The coating agent may be preferably 0.01 to 10 parts by weight, more preferably 0.1 to 1 part by weight, based on 100 parts by weight of the total positive electrode active material. Within this range, the coating agent has the effect of improving structural stability and electrochemical performance while maintaining the properties of the positive electrode active material itself.
[0092] The heat treatment time is preferably 1 to 16 hours, more preferably 3 to 7 hours. Within this range, the properties of the positive electrode active material itself are maintained, while the structural stability and electrochemical performance are improved.
[0093] The coating agent may be, for example, spherical, plate-like, angular, or needle-like, and such shapes can be adjusted, for example, by changing process conditions during the manufacturing process. The specific shape of each shape is not particularly limited as long as it follows the definition commonly accepted in the technical field to which the present invention belongs.
[0094] The coating agent preferably has an average diameter of 1 to 1000 nm and a specific surface area of 10 to 100 m 2 / g, and more preferably, the average diameter is 10 to 100 nm and the specific surface area is 20 to 100 m 2 / g, and within this range, the particles are uniformly attached to the surface of the positive electrode active material, imparting structural stability to the positive electrode active material, thereby improving the problems of deterioration in life characteristics and electrochemical performance due to lattice deformation and collapse of the crystal structure of the positive electrode active material.
[0095] In this description, the average diameter can be measured by a measurement method commonly used in the technical field to which the present invention pertains, for example, by using a laser diffraction method. Specifically, particles of a positive electrode active material can be dispersed in a dispersion medium and then introduced into a commercially available laser diffraction particle size analyzer such as a Microtrac MT 3000. Ultrasonic waves of about 28 kHz and an output of 60 W can be irradiated to calculate the average particle size (D50) based on 50% of the particle size distribution measured by the analyzer.
[0096] In this description, the specific surface area can be measured by a measurement method commonly used in the technical field to which the present invention pertains, for example, by the BET (Brunauer-Emmett-Teller) method, and specifically, can be calculated from the amount of nitrogen gas adsorption at liquid nitrogen temperature (77 K) using a BELSORP-mino II from BEL Japan.
[0097] FIG. 9 below is a flowchart showing a process for regenerating a positive electrode active material according to one embodiment of the present invention.
[0098] Referring to Fig. 9, first, cathode scraps are prepared (step S10). For example, a slurry prepared by mixing an LCO-based lithium composite transition metal oxide, carbon black, and polyvinylidene fluoride with N-methyl pyrrolidone (NMP) is coated on aluminum foil and dried in a vacuum oven at about 120°C to prepare a cathode sheet. After punching out cathode plates of a certain size, the remaining cathode scraps can be prepared.
[0099] The cathode scrap has a cathode active material layer on an aluminum foil, and after the solvent evaporates, the cathode active material layer has a structure in which the cathode active material and the conductive material are bound by the binder. Therefore, when the binder is removed, the cathode active material is separated from the aluminum foil.
[0100] Next, the prepared cathode scrap is crushed to an appropriate size (step S20). Here, crushing includes cutting or shredding the cathode scrap to a size that is easy to handle. As a specific example, the crushed cathode scrap may be 1 cm x 1 cm in size. For example, the crushing may be performed using various dry crushing equipment such as a hand mill, pin mill, disc mill, cutting mill, or hammer mill, or a high-speed cutter may be used to increase productivity.
[0101] The decision as to whether or not to crush the cathode scrap and the size of the pieces may be made in consideration of the handling of the cathode scrap and the properties required by the equipment used in the subsequent steps. For example, when using equipment capable of continuous processing, the cathode scrap should be crushed into smaller pieces because good fluidity is required.
[0102] Next, the positive electrode scrap is heat-treated in air (step S30), where the heat treatment is carried out to thermally decompose the binder in the active material layer.
[0103] Through the heat treatment in air, the binder and conductive material in the active material layer are thermally decomposed into CO2 and HO and removed. Because the binder is removed, the positive electrode active material is separated from the current collector, and the separated positive electrode active material can be easily sorted in powder form. Therefore, even with step S30 alone, the active material layer can be separated from the current collector, and the positive electrode active material in the active material layer can be recovered in powder form.
[0104] It is important that the heat treatment be performed in air. However, if the heat treatment is performed in a reducing or inert gas atmosphere, the binder and conductive material will carbonize without being thermally decomposed. Carbonization leaves carbon components on the surface of the cathode active material, reducing the performance of the recycled cathode active material. However, if the heat treatment is performed in air, the carbon components in the binder and conductive material react with oxygen and disappear as gases such as CO and CO2, removing both the binder and conductive material.
[0105] The heat treatment is preferably carried out at 300 to 650°C, specifically at 550°C. If the temperature is lower than 300°C, it is difficult to remove the binder, making it impossible to separate the current collector. If the temperature exceeds 650°C, the current collector melts, making it impossible to separate the current collector.
[0106] The heat treatment is preferably carried out at a temperature increase rate of 1 to 20°C / min, more preferably 3 to 10°C / min, specifically 5°C / min. Within this range, the heat treatment can be carried out without placing strain on the heat treatment equipment, and there are advantages in that no thermal shock or the like is caused to the cathode scrap.
[0107] The heat treatment can be carried out for a period of time sufficient to thermally decompose the binder, preferably for 30 minutes or more, more preferably for 30 minutes to 5 hours, and specifically for about 30 minutes. Within this range, the binder is sufficiently thermally decomposed and the thermal decomposition efficiency is excellent.
[0108] The heat treatment may be carried out using various types of furnaces, for example, a box-type furnace, or, in consideration of productivity, a rotary kiln capable of continuous treatment.
[0109] After the heat treatment, the material can be cooled slowly or rapidly in the air.
[0110] Next, as a surface modification step, the recovered positive electrode active material is washed with water containing an ionic solid salt (step S40).
[0111] The washing with water containing the ionic solid salt effectively removes foreign matter that may have formed on the surface of the positive electrode active material during the heat treatment step (S30), preventing foreign matter from remaining on the surface of the regenerated positive electrode active material and minimizing the loss of a functional coating layer, such as an F compound layer, formed on the initial raw material. The functional coating layer is applied to the initial raw material to ensure long-life and high-voltage characteristics.
[0112] It is also important to use water containing an ionic solid salt as the cleaning solution. However, if an aqueous solution of sulfuric acid or hydrochloric acid is used, it will be possible to clean foreign matter such as fluorine (F) compounds from the surface of the positive electrode active material, but it will dissolve transition metals such as Co and Mg present in the positive electrode active material, thereby reducing the performance of the regenerated positive electrode active material.
[0113] However, water containing the ionic solid salt is preferable because it is safe and inexpensive, can remove binders and the like that may remain in trace amounts even after the thermal decomposition in step S30 without losing other elements, and does not elute transition metals present in the positive electrode active material.
[0114] The ionic solid salt may be at least one selected from the group consisting of MgSO, Mg(NO), and Ca(NO). In this case, there are advantages in that foreign matter generated on the surface of the positive electrode active material during the heat treatment step is effectively removed and loss of the functional coating layer formed on the initial raw material is minimized.
[0115] The water containing the ionic solid salt may be used in the form of an aqueous solution in which the ionic solid salt is dissolved in water, or in the form of a powder dispersed in water.
[0116] The ionic solid salt reacts with LiF formed on the surface of the positive electrode active material to form a complex compound, which remains in the form of a precipitate on the surface of the positive electrode active material or in water containing the ionic solid salt, and can be easily removed.
[0117] Specifically, the ionic solid salt can be used in an amount of 1.5 to 5.5 parts by weight per 100 parts by weight of the recovered positive electrode active material.
[0118] For the washing, for example, water containing an ionic solid salt can be used in an amount 1 to 40 times by weight relative to the weight of the positive electrode active material to be washed.
[0119] The cleaning is performed, for example, by stirring the recovered cathode active material and the cleaning solution together, which is not particularly limited and may be mechanical or ultrasonic.
[0120] The washing is carried out, for example, at 300 to 700 rpm for 5 to 20 minutes, and within this range, it is effective to prevent a decrease in battery capacity due to excessive elution of lithium.
[0121] In this description, the reason for washing the recovered cathode active material with water containing an ionic solid salt is to perform surface modification by removing heat treatment by-products, such as LiF and metal fluorides, present on the surface of the recovered cathode active material. During the heat treatment in step S30, the binder and conductive material in the active material layer are vaporized and removed as CO2 and HO. During this process, CO2 and HO may react with lithium on the surface of the cathode active material to form Li2CO3 and LiOH. Furthermore, F present in binders such as PVdF may react with lithium and other metal elements constituting the cathode active material to form LiF or metal fluorides. If such LiF or metal fluorides remain on the surface of the cathode active material, battery performance may deteriorate during reuse.
[0122] After the collected positive electrode active material and the water containing the ionic solid salt are stirred or mixed, the resulting positive electrode active material slurry is filtered or the supernatant is decanted and discarded to obtain the solid positive electrode active material.
[0123] The obtained positive electrode active material is preferably dried, for example, by vacuum drying.
[0124] Next, a lithium precursor is added to the washed positive electrode active material, and annealing is performed (step S50).
[0125] Because lithium loss occurs within the positive electrode active material during steps S30 and S40, this loss of lithium is replenished in step S50. Furthermore, because a deformed structure (e.g., Co3O4 in the case of an LCO active material) may develop on the surface of the positive electrode active material during these steps, step S50 involves annealing to restore the crystalline structure of the positive electrode active material, thereby improving the properties of the regenerated positive electrode active material or restoring it to the level of a virgin positive electrode active material. Here, "virgin" is the opposite concept of "regenerated," meaning that the material is newly produced, and is the same term as "raw material" used in the examples.
[0126] As the lithium precursor, Li2CO3 is specifically used.
[0127] The lithium precursor is preferably added in an amount corresponding to the molar ratio of lithium lost relative to the molar ratio of lithium to other metals in the new cathode active material used in the cathode active material layer. Adding an amount of lithium precursor that is excessively greater than the amount of lost lithium leaves unreacted lithium precursor in the regenerated cathode active material, which increases resistance, so it is necessary to add an appropriate amount of lithium precursor. For example, if the molar ratio of lithium to other metals in the new cathode active material is 1, the lithium precursor can be added in an amount that results in a lithium molar ratio of 0.001 to 0.4, preferably 0.01 to 0.2.
[0128] The annealing is carried out in air at, for example, 400 to 1000°C, preferably 600 to 900°C, and this temperature must be varied within a limited range depending on the type of lithium precursor.
[0129] The annealing temperature is preferably a temperature exceeding the melting point of the lithium precursor. However, temperatures exceeding 1000°C may cause thermal decomposition of the positive electrode active material, resulting in a decrease in performance, and therefore should not exceed 1000°C. Therefore, when Li2CO3 is used as the lithium precursor, the annealing temperature may be suitably 700 to 900°C, more preferably 720 to 780°C, and most preferably 740 to 760°C. Furthermore, when Li2CO3 is used as the lithium precursor, the annealing temperature may be suitably 700 to 900°C, more preferably 720 to 780°C, and most preferably 740 to 760°C.
[0130] The annealing time is, for example, 1 hour or more, preferably 15 hours or less, and more preferably 4 to 6 hours. A longer annealing time may allow sufficient recovery of the crystal structure, but even if annealing is performed for a long period of time, the performance is not significantly affected. The annealing equipment may be the same as or similar to that used in the heat treatment step S30.
[0131] The annealing step is safe and inexpensive, and restores the crystalline structure, i.e., improves the crystallinity, thereby restoring the battery characteristics of the regenerated positive electrode active material.
[0132] The recycled cathode active material obtained through the above-described cathode active material recycling step has a particle size distribution similar to that of the virgin cathode active material, and does not contain any carbon components on the surface that are generated by carbonization of the binder or conductive material. Therefore, it can be used to manufacture a cathode 100% as is or by mixing with virgin materials without any additional processing.
[0133] Next, as an optional step, the annealed positive electrode active material can be further subjected to a surface coating (S60).
[0134] For example, the surface coating is performed by mixing a coating agent and then heat-treating the mixture at 100 to 1200°C. If the heat treatment temperature is less than 100°C, a surface protective layer made of a different metal is not formed through the surface coating, and if the heat treatment temperature is more than 1200°C, the battery performance is reduced due to thermal decomposition of the positive electrode active material.
[0135] The coating agent may be, for example, a metal oxide or a metal salt containing carbon.
[0136] Specifically, when a metal oxide such as B, W, or BW is mixed with a positive electrode active material and then heat-treated, a lithium boron oxide layer can be formed on the surface of the active material, which acts as a surface protection layer.
[0137] For reference, if the molar ratio of lithium to other metals in the positive electrode active material is set to 1:1 in the previous annealing step S50, and the lithium in the positive electrode active material reacts with the coating agent, causing the molar ratio of lithium to other metals in the positive electrode active material to decrease below 1:1, the battery's capacity cannot be fully realized. Therefore, the missing lithium is not only added in the previous step S50 to achieve a 1:1 molar ratio of lithium to other metals in the positive electrode active material, but also added in excess so that the lithium is present in an amount of 0.0001 to 0.1 molar ratio greater than the other metals in the positive electrode active material. This ensures that the molar ratio of lithium to other metals in the positive electrode active material is 1:1 during the surface coating step S60, and also forms a surface protective layer.
[0138] Specifically, the lithium added in excess of about 0.0001 to 0.1 molar ratio in step S50 reacts with metal oxides such as B, W, and BW in step S60, and the molar ratio of lithium to other metals in the positive electrode active material does not decrease below 1 (lithium):1 (other metals), so no decrease in capacity occurs.
[0139] Regenerated cathode active material The recycled cathode active material of the present invention is characterized by being produced by the above-described method for regenerating a cathode active material. In this case, the F component remaining on the surface of the recycled cathode active material after the heat treatment step is thoroughly removed with water containing an ionic solid salt, minimizing the loss of the functional coating layer formed on the initial raw material, thereby significantly improving the rate performance.
[0140] In addition, the regenerated positive electrode active material of the present invention may preferably include at least one selected from the group consisting of lithium cobalt oxides such as LCO, lithium manganese oxides such as LiMnO or LiMnO, lithium iron phosphate compounds such as LiFePO, lithium nickel cobalt aluminum oxide (NCA), lithium nickel cobalt aluminum oxide (NCA), lithium nickel oxides such as LiNiO, nickel manganese-based lithium composite metal oxides in which part of the nickel (Ni) in the lithium nickel oxide is substituted with manganese (Mn), and NCM-based lithium composite transition metal oxides in which part of the nickel (Ni) in the lithium nickel oxide is substituted with manganese (Mn) and cobalt (Co). In this case, excellent electrochemical performance, resistance characteristics, and capacity characteristics can be obtained.
[0141] As a more specific example, the regenerated positive electrode active material may be represented by the following chemical formula 1: [Chemical formula 1] Li a Ni x Mn y Co z M w O 2+δ (In the chemical formula 1, M contains one or more selected from the group consisting of B, W, Al, Ti, and Mg, 1 < a ≤ 1.1, 0 < x < 0.95, 0 < y < 0.8, 0 < z < 1.0, 0 ≤ w ≤ 0.1, -0.02 ≤ δ ≤ 0.02, and x + y + z + w = 1). It contains a compound represented by the formula, contains 1 to 10,000 ppm of Al2O3, and is characterized in that the surface is coated with a coating agent containing metal or carbon. In this case, there is an effect of excellent electrochemical performance, resistance characteristics, capacitance characteristics, etc.).
[0142] The regenerated cathode active material may preferably be coated with a coating agent containing metal or carbon. In this case, without chemical and physical changes in the cathode active material itself, the structural stability of the cathode active material is improved, so that electrochemical characteristics such as output performance, life characteristics, and capacitance are improved. The amount of residual lithium is reduced by substitution with different elements on the surface of the cathode active material, and due to the effect of pH reduction, the physicochemical characteristics are also improved.
[0143] The regenerated cathode active material of the present invention can include all the contents of the above-described method for regenerating the cathode active material. Therefore, duplicate descriptions thereof are omitted here.
[0144] Hereinafter, preferred examples are presented to assist in understanding the present invention. However, it is obvious to those skilled in the art that the following examples are merely illustrative of the present invention, and various changes and modifications are possible within the scope of the present invention and the scope of the technical idea. It is natural that such changes and modifications belong to the scope of the appended claims.
[0145] [Examples] Example 1 The cathode scrap (current collector: aluminum foil, cathode active material: lithium cobalt oxide) discarded after punching out the cathode plates was crushed and heat-treated in air at 570°C for 30 minutes to remove the binder and conductive material. The current collector and cathode active material were then separated and recovered. The temperature was increased at a rate of 5°C / min to reach the heat treatment temperature. The LiF content of the recovered cathode active material was measured using ICP-OES analysis and was found to be 5200 ppm.
[0146] To remove foreign materials such as LiF and metal fluorine present on the surface, 15 g of the recovered cathode active material was added to 450 g of water (30 times the weight of the cathode active material) containing 0.3326 g of anhydrous MgSO4 as an ionic solid salt, and stirred for 10 minutes at a stirring speed of 500 rpm. 0.3326 g of anhydrous MgSO4 as an ionic solid salt corresponds to 0.5 moles per mole of LiF present on the surface of the recovered cathode active material.
[0147] After the stirring was completed, the mixture was rinsed with 150 g of deionized water (DIW) (10 times the weight of the positive electrode active material). After the rinsing, the positive electrode active material slurry was filtered using a 0.3 μm filter paper to recover the solid positive electrode active material. The recovered positive electrode active material was dried under vacuum.
[0148] The lithium precursor Li2CO3 was added to the dried cathode active material in an amount such that the molar ratio of lithium was 0.02, based on the molar ratio of lithium to other metals in the raw cathode active material. The mixture was sieved twice using a sieve with a mesh size of #325, and then annealed in air at 750°C for 5 hours.
[0149] Example 2 A regenerated positive electrode active material was produced in the same manner as in Example 1, except that the amount of ionic solid salt MgSO was changed from 0.3326 g to 0.6652 g. 0.6652 g of anhydrous MgSO as the ionic solid salt corresponded to 1 mole of LiF per mole of LiF present on the surface of the recovered positive electrode active material.
[0150] Example 3 A recycled positive electrode active material was produced in the same manner as in Example 1, except that 15 g of the recovered positive electrode active material was added to 450 g of water (30 times the weight of the positive electrode active material) together with 0.3326 g of ionic solid salt MgSO4.
[0151] Example 4 A recycled cathode active material was prepared in the same manner as in Example 1, except that 0.3326 g of the ionic solid salt MgSO was replaced with 0.7085 g of Mg(NO) 6H O. The 0.7085 g of Mg(NO) 6H O corresponded to 0.5 mol per 1 mol of LiF present on the surface of the recovered cathode active material.
[0152] Example 5 A recycled cathode active material was prepared in the same manner as in Example 1, except that 0.3326 g of the ionic solid salt MgSO was replaced with 0.6525 g of Ca(NO) 4H O. The 0.6525 g of Ca(NO) 4H O corresponded to 0.5 mol per 1 mol of LiF present on the surface of the recovered cathode active material.
[0153] Comparative Example 1 15g of LCO virgin material (Ref.) with a surface fluorine (F) layer was mixed with 450g of distilled water, stirred vigorously for 10 minutes, washed with water, and then vacuum filtered using 3µm filter paper. After washing with water, ICP-OES analysis confirmed that 2mol% of Li had been lost compared to the LCO virgin material (Ref.). The recovered filter cake was dried in a vacuum oven at 100°C and then heat-treated in an air atmosphere at 750°C for 5 hours to recover the positive electrode active material.
[0154] Comparative Example 2 The same procedure as in Comparative Example 1 was carried out except that before the heat treatment at 750°C, 0.02 mol of Li2CO3 was added, which was equivalent to 2 mol% of Li lost by water washing, and solid-state mixing was performed, followed by heat treatment.
[0155] Comparative Example 3 15 g of the recovered cathode active material from Example 1 was mixed with 450 g of distilled water, vigorously stirred for 10 minutes, and then filtered under reduced pressure using a 3 μm filter paper. The recovered filter cake was dried in a vacuum oven at 100°C and then heat-treated in an air atmosphere at 750°C for 5 hours, after which the cathode active material was recovered.
[0156] Reference example We used LCO new living material (Ref.) with a fluorine layer formed on the surface.
[0157] [Test example] The properties of the regenerated positive electrode active materials obtained in Examples 1 to 5 and Comparative Examples 1 to 3, and the new positive electrode active material of the Reference Example, were measured by the following methods, and the results are shown in Table 1 below and FIGS. *ICP-OES analysis: Using an ICP-OES analyzer (Inductively Coupled Plasma Optical Emission Spectroscophotometer), the content of LiF produced in the recovered positive electrode active material, the ratio of lithium to other metals in the active material, and the content (mg / kg) of specific elements such as F were measured. Measurements can be made using a general ICP-OES analyzer commonly used in laboratories, and there is no deviation due to the measurement device or method. *Cell evaluation: 96% by weight of recycled or new positive electrode active material, 2% by weight of carbon black (conductive material), and 2% by weight of PVdF (binder) were weighed and mixed with NMP to prepare a slurry. This was coated on aluminum foil to prepare a positive electrode, and a coin half cell (CHC) was fabricated. The electrochemical performance was evaluated at 25°C and a voltage of 3 to 4.55V.
[0158] [Table 1]
[0159] As shown in Table 1, the regenerated positive electrode active materials (Examples 1 to 5) according to the present invention have superior charge / discharge capacities and efficiencies compared to Comparative Examples 1 to 3, which did not undergo the cleaning step according to the present invention, and are similar to or superior to the virgin positive electrode active material (Reference Example).
[0160] Figure 2 below is a graph showing the rate performance as a function of the number of cycles, which is the result of cell evaluation of the cathode active material of the Reference Example and the cathode active material of Comparative Example 1. This graph examines rate performance by evaluating capacity as a function of the number of cycles repeated at different currents. For reference, in the graph of Figure 2, the horizontal axis represents the number of cycles, and the vertical axis represents capacity.
[0161] Referring to Figure 2, the recycled cathode active material prepared in Comparative Example 1 exhibited lower output performance across all cycle ranges tested compared to the cathode active material of the Reference Example. This is presumably due to the removal of the surface coating layer during water washing, resulting in the elution of Li. Furthermore, ICP-OES analysis of the recycled cathode active material prepared in Comparative Example 1 confirmed that 2 mol% of Li had been lost after water washing.
[0162] Figure 3 below is a graph showing the rate performance as a function of the number of cycles, which is the result of cell evaluation of the recycled cathode active material prepared in Comparative Example 1 and the recycled cathode active material prepared in Comparative Example 2. The cathode active material prepared in Comparative Example 2 was prepared by adding an amount of Li2CO3 equivalent to the amount of Li lost during washing with water, performing solid-state mixing, and then calcining.
[0163] 3, it was confirmed that the capacity of the recycled cathode active material prepared in Comparative Example 2 was partially restored compared to the recycled cathode active material prepared in Comparative Example 1, but was lower than that of the cathode active material of Reference Example 1. This can be inferred from the fact that the surface F (fluorine) layer that had disappeared due to washing with water could not be completely restored.
[0164] FIG. 4 below is a graph showing the results of cell evaluation of the recycled positive electrode active material prepared in Example 1 and the recycled positive electrode active material prepared in Comparative Example 3, illustrating the rate performance as a function of the number of cycles.
[0165] Referring to FIG. 4, the recycled positive electrode active material prepared in Example 1 exhibited improved output performance in all cycle ranges tested, compared to the positive electrode active material of Comparative Example 3.
[0166] FIG. 5 below is a graph showing the results of cell evaluation of the recycled positive electrode active material prepared in Example 2 and the positive electrode active material of Comparative Example 3, showing the rate performance as a function of the number of cycles.
[0167] Referring to FIG. 5, the recycled positive electrode active material prepared in Example 2 exhibited improved output performance in all cycle ranges tested compared to the recycled positive electrode active material prepared in Comparative Example 3.
[0168] FIG. 6 below shows the results of cell evaluation of the recycled positive electrode active materials prepared in Examples 1 and 3 and the recycled positive electrode active material prepared in Comparative Example 3, and is a graph showing the rate performance as a function of the number of cycles.
[0169] 6, the recycled cathode active materials prepared in Examples 1 and 3 exhibited improved output performance in all cycle ranges tested compared to the recycled cathode active material prepared in Comparative Example 3. In addition, the recycled cathode active material prepared in Example 3 and the recycled cathode active material prepared in Example 1 exhibited similar or identical output performance in all cycle ranges tested. This indicates that similar or identical effects are achieved whether MgSO4 is dissolved in water or added in powder form to water together with the cathode active material.
[0170] FIG. 7 below shows the results of cell evaluation of the recycled positive electrode active materials prepared in Examples 1 and 4 and the recycled positive electrode active material prepared in Comparative Example 3, and is a graph showing the rate performance as a function of the number of cycles.
[0171] Referring to FIG. 7, the recycled cathode active material prepared in Example 4 had a capacity 1 mAh / g lower than that of the cathode active material prepared in Example 1, but had improved output performance in all cycle ranges tested compared to the recycled cathode active material prepared in Comparative Example 3.
[0172] FIG. 8 below shows the results of cell evaluation of the recycled positive electrode active materials prepared in Examples 1 and 5 and the recycled positive electrode active material prepared in Comparative Example 3, and is a graph showing the rate performance as a function of the number of cycles.
[0173] Referring to FIG. 8, the recycled cathode active material prepared in Example 5 had a slightly lower capacity than the recycled cathode active material prepared in Example 1, but had improved output performance in the range of 4 cycles or more compared to the recycled cathode active material prepared in Comparative Example 3. [Explanation of symbols]
[0174] 10 Current collector 20 Active material layer 30 Positive electrode sheet 40 positive electrode plate 50 cathode scrap
Claims
1. (a) subjecting a used positive electrode of a lithium secondary battery, which includes a current collector and a positive electrode active material layer coated on the current collector, to a heat treatment at 300 to 650° C. in air to recover a positive electrode active material; (b) washing the recovered positive electrode active material with water containing an ionic solid salt; (c) adding a lithium precursor to the washed cathode active material and annealing in air at 400-1000° C.; The method for regenerating a positive electrode active material, wherein the ionic solid salt is at least one selected from the group consisting of MgSO 4 , Mg(NO 3 ) 2 , and Ca(NO 3 ) 2 .
2. 2. The method for regenerating a positive electrode active material according to claim 1, wherein the discarded positive electrode in step (a) is a positive electrode separated from a lithium secondary battery discarded after use, a defective positive electrode sheet generated in a manufacturing process of a lithium secondary battery, or a positive electrode scrap remaining after punching a positive electrode plate from a positive electrode sheet of a lithium secondary battery.
3. 2. The method for regenerating a positive electrode active material according to claim 1, wherein the positive electrode active material layer includes at least one selected from the group consisting of lithium cobalt oxide, lithium manganese oxide, lithium iron phosphate compound, lithium nickel cobalt aluminum oxide, lithium nickel oxide, a nickel manganese-based lithium composite metal oxide in which part of the nickel (Ni) in the lithium nickel oxide is replaced with manganese (Mn), and an NCM-based lithium composite transition metal oxide in which part of the nickel (Ni) in the lithium nickel oxide is replaced with manganese (Mn) and cobalt (Co).
4. The method for regenerating a positive electrode active material according to claim 1, wherein in the washing step (b), water containing an ionic solid salt is used in an amount of 1 to 40 times the weight of the recovered positive electrode active material.
5. 2. The method for regenerating a positive electrode active material according to claim 1, wherein the water containing the ionic solid salt in step (b) is an aqueous solution in which the ionic solid salt is dissolved in water, or the ionic solid salt is in a powder-like state dispersed in water.
6. The method for regenerating a positive electrode active material according to claim 1 , wherein the ionic solid salt in step (b) forms a complex compound on the surface of the positive electrode active material.
7. The method for regenerating a positive electrode active material according to claim 1, wherein the ionic solid salt in step (b) is used in an amount of 0.5 to 2 moles per mole of LiF produced in the recovered positive electrode active material.
8. The method for regenerating a positive electrode active material according to claim 1 , wherein the washing in the step (b) includes stirring the recovered positive electrode active material with water containing an ionic solid salt.
9. The method for regenerating a positive electrode active material according to claim 1 , wherein the step (b) includes a process of drying the washed positive electrode active material.
10. The lithium precursor in step (c) is LiOH, Li 2 CO 3 , LiNO 3 and Li 2 2. The method for regenerating a positive electrode active material according to claim 1, wherein the positive electrode active material is one or more selected from the group consisting of O.
11. 2. The method for regenerating a positive electrode active material according to claim 1, wherein the lithium precursor in step (c) is added in an amount that is at least a molar ratio of lithium in the positive electrode active material in step (a) that is reduced based on the amount of lithium in the washed positive electrode active material.
12. The method for regenerating a positive electrode active material according to claim 1 , wherein the annealing temperature in step (c) is a temperature exceeding the melting point of the lithium precursor.
13. The method for regenerating a positive electrode active material according to claim 1, further comprising the step of (d) mixing the annealed positive electrode active material with a coating agent and then coating the mixture by heat treatment at 100 to 1200°C.
Citation Information
Patent Citations
Method for recovering leftover materials of lithium ion battery cathodes
CN105870533A
Method for separating and recovering valuable material from used lithium ion battery
JP2012229481A
Positive electrode active material recovery method
JP2015185471A
Method for regenerating lithium composite oxide, lithium composite oxide, electrochemical device, and lithium ion secondary battery
JP2016085953A
Processing method of used lithium ion battery
JP2016149330A